Larger Than Life : Movie Stars of the 1950s - Wojcik, Pamela Robertson, 1964-; White, Susan; Solomon, Matthew; Sandler, Barry; Pugh, Tison; Pomerance, Murray, 1946-; McLean, Adrienne L.; Lawrence, Amy, 1957-; Krutnik, Frank, 1956-; Hirsch, Foster; Brown, William, 1977-; Palmer, R. Barton, 1946- (Book collections on Project MUSE., 2010)
The constellation of Hollywood stars burned brightly in the 1950s, even as the industry fell on hard economic times. Major artists of the 1940s continued to exert a magical appeal but the younger generation of moviegoers was soon enthralled by an emerging cast, led by James Dean and Marlon Brando. They, among others, ushered in a provocative acting style, "the Method," bringing hard-edged, realistic performances to the screen. Larger Than Life offers a comprehensive view of the star system in 1950s Hollywood and also in-depth discussions of the decade's major stars.